VD_FINDINFO HC / 2013 / 437 vom 18. Juli 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, REVENU ANNUEL MOYEN, REVENU DÉTERMINANT | 163 CC, 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC, 308 al. 1 let. b CPC (CH)